Genetics research of apoptosis and BRCA1 gene mutations in patients from family with hereditary breast cancer - Kulig, Andrzej; Smolarz, Beata; Westfal, Bogusław; Kozłowska, Elżbieta; Romanowicz-Makowska, Hanna; Zadrożny, Marek; Pertyński, Tomasz; Stetkiewicz, Tomasz (Menopause Review/Przegląd Menopauzalny, 2004)
Purpose: Susceptibility to breast cancer appears to be linked to germ-line mutations in genes causing various familial cancer syndromes. Moreover apoptotic cell death plays a central role in the pathogenesis and disease progression of this cancer. The objectives of this study were to determine apoptosis and the frequency of BRCA1 germ-line mutations in patients with family history of breast cancer. Materials and methods: The study population consisted of 30 patients from breast cancer family and 30 control samples. Patients completed a family history questionnaire and provided blood for mutation analysis. Results: Out of the 30 investigated samples, 11 (or 37%) were found to be apoptosis positive compared as 13% control. One Ex20insC and two ExII17delA mutations of BRCA1 gene were identified in apoptosis positive samples from breast cancer families. Conlusion: Genetic alterations seem to be a risk factor of breast cancer in subjects belonged to breast cancer families with high incidence of this cancer. The lack of detectable germ-line mutations in most cases suggests that there are probably additional, as yet unidentified genes predisposing to this disease.